BRIKET SEKAM PADI SEBAGAI ENERGI ALTERNATIF DI DESA BANDINGAN, BAWANG BANJARNEGARA - Mahmudati, Rina; Rahmadani, Muslifah; Setiadi, Tiana (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
Rice husk is a type of food that is very valuable for food security in cultivation in various parts of the world. The agricultural, harvesting and rice processing processes are an integral part. The evaluation was carried out with the aim of knowing the follow-up to the implementation of this training. From the evaluation, it was found that training in briquette making would be followed up by the Bandingan Village farmer group together with students. Based on the results of the implementation of outreach activities, it can be concluded that: 1) Provide knowledge and awareness to the people of Bandingan Village, Bawang sub-district regarding the use of briquettes from rice husk waste. 2) The creation of processed rice husk waste into briquettes has economic value so that it can be used as an additional alternative to help the economy of the community around the comparison village of Bawang District, Banjarnegara Regency.